Green spaces between theory and reality. Case study of the city of M'sila - Algeria - Seghiri, Djamel; Khalfalleh, Boudjamea; Layeb, Hafid (Technium Social Sciences Journal, 2022)
The green areas are considered as an integral part of the planning of the urban environment as they are an integral part of the city and include several important functional, aesthetic and environmental dimensions. It is achieved through the adoption of a coordinated and systematic approach and planning and is also influenced by a range of planning, technical and managerial factors.The aim of this research is to study and clarify the most important current problems that afflict the green spaces in the city of M'sila at the level of their urban spaces on one hand and to highlight the reasons that led to this situation. Based on a methodology based on a descriptive analytical approach to produce recommendations that would achieve the objectives of this paper.